Designing a Blessed Future: Maqashid Syariah and Financial Planning for Holistic Well-Being - Anista , Jodang Setia Adi; Al Idrus, Salim; Munir, Misbahul (AKRUAL: JURNAL AKUNTANSI, 2024)
Research Background: The planning used is not solely for the purpose of seeking profit, but rather how we use our finances from now until the future, taking into account several needs so that everything will have a clear purpose for the use of finances and not be wasteful. Objectives: This article discusses financial planning based on maqoshid syariah, which includes a discussion of how we manage our finances so that they are not wasted. Methods: This research is qualitative and descriptive in nature, with data obtained from literature reviews relevant to the research title. Data analysis methods include descriptive and comparative analysis. Results: The results of this research are how maqoshid syariah becomes the foundation of the economy to achieve prosperity, by regulating human needs and directing the use of finances in accordance with religious teachings. Implication: How maqoshid syariah serves as the foundation for financial planning involves allocating several steps, such as short-term, medium-term, and long-term planning. With properly allocated planning, the results will lead to human well-being, both physically and spiritually. To meet needs equitably, balanced management of needs is required, ensuring that all allocations for needs are fulfilled and achieved.